Advanced monitoring techniques for complex process variability in manufacturing industry - Maman A. Djauhari (Penerbit Universiti Putra Malaysia, 2016)
Manufacturing industries Manufacturing industry is a dominant sector of economic development in a nation. However, the competition in this sector is very tight all over the world and only industry which provides high quality of process and products will survive. This book is written to fulfill the need of manufacturing industries to monitor any complex process variability in a comprehensive manner. It is dedicated to all quality professionals, industrial engineers, industrial managers, researchers, lecturers, quality practitioners, and students who are eager to take part in the tight competition of modern industries.